Examining the Impact of Violence in the Name of Islam on the Stability of Islamic Education Worldwide - Muaripin, Ary Maulana; Pratama, Dhika Arya; Suhartini, Andewi (Yayasan Rahmat Islamiyah, 2025)
Violence in the name of religion, particularly Islam, has drawn significant global attention in recent decades. This study aims to examine the impact of violence committed in the name of Islam on the stability of Islamic education worldwide. Using a qualitative literature-based approach, the research finds that such violence disrupts educational systems, diminishes public trust in Islamic educational institutions, and fosters negative stigma against Muslims. The findings highlight the importance of strengthening inclusive and tolerant Islamic education to address these challenges.